Clinical and genetic characterization of a Taiwanese cohort with spastic paraparesis combined with cerebellar involvement - Lan, Min-Yu; Lu, Chin-Song; Wu, Shey-Lin; Chen, Ying-Fa; Sung, Yueh-Feng; Tu, Min-Chien; Chang, Yung-Yee (Frontiers in Neurology, 2022)
Hereditary spastic paraplegias (HSPs) are a heterogeneous group of neurodegenerative disorders clinically characterized by progressive lower-limb spasticity. Cerebellar ataxia commonly co-occurs with complicated HSPs. HSP with concurrent cerebellar ataxia has significant clinical and genetic overlaps with hereditary cerebellar ataxia (HCA) and other inherited neurological diseases, adding to the challenge of planning genetic testing for the disease. In this study, we characterized clinical features of a cohort of 24 patients (male/female: 15/9) from 22 families who presented spastic paraparesis combined with cerebellar involvement, with a median disease onset age 20.5 (range 5 to 53) years. Aside from the core phenotype, 18 (75%) patients had additional neuropsychiatric and systemic manifestations. A stepwise genetic testing strategy stratified by mode of inheritance, distinct neuroimaging features (e.g. thin corpus callosum), population-specific prevalence and whole-exome sequencing was utilized to investigate the genetic etiology. Causative mutations in up to 10 genes traditionally related to HSP, HCA and other neurogenetic diseases (autosomal recessive spastic ataxia of Charlevoix-Saguenay, neurodegeneration with brain iron accumulation, and progressive encephalopathy with brain atrophy and thin corpus callosum) were detected in 16 (73%) of the 22 pedigrees. Our study revealed the genetic complexity of HSP combined with cerebellar involvement. In contrast to the marked genetic diversity, the functions of the causative genes are restricted to a limited number of physiological themes. The functional overlap might reflect common underlying pathogenic mechanisms, to which the corticospinal tract and cerebellar neuron circuits may be especially vulnerable.